2018
DOI: 10.1111/acps.12959
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors predicting treatment resistant depression: affirmative results from the European multicenter study

Abstract: Objectives Clinical variables were investigated in the ‘treatment resistant depression ( TRD )‐ III ’ sample to replicate earlier findings by the European research consortium ‘Group for the Study of Resistant Depression’ ( GSRD ) and enable cross‐sample prediction of treatment outcome in TRD . Experimental procedures TRD was defined by a Montgomery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
85
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 39 publications
11
85
1
Order By: Relevance
“…According to modern studies, depressive disorders are characterized by polymorphism of symptoms, difficulty of diagnosis and resistance to therapy [4][5][6][7]. In this regard, it is important to study the clinical phenomenology of depressive disorders at the present stage, which can be the basis for the development of effective preventive measures [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…According to modern studies, depressive disorders are characterized by polymorphism of symptoms, difficulty of diagnosis and resistance to therapy [4][5][6][7]. In this regard, it is important to study the clinical phenomenology of depressive disorders at the present stage, which can be the basis for the development of effective preventive measures [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The term treatment-resistant depression (TRD) has been used increasingly over the last decades and usually translates into MDD in which the patient's condition has not responded to two or more adequate treatment trials (Conway, George, & Sackeim, 2017;Ruhe, van Rooijen, Spijker, Peeters, & Schene, 2012). Depending on whether response or remission of symptoms is used in the definition of TRD, the proportion among patients with MDD meeting these criteria ranged between 35% and 64% in the large clinical data sets from the Sequenced Treatment Alternatives to Relieve Depression (STAR Ã D) study and the European Group for the Study of Resistant Depression samples (Kautzky et al, 2019;Rush, Trivedi, Wisniewski, Nierenberg et al, 2006Souery et al, 2007). Despite this, studies with long-term follow-up of patients with TRD are scarce and do not include risk factor analyses of adverse outcomes such as death or suicide (Dunner et al, 2006;Fekadu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of TRD has generated a substantial amount of study and collaboration that has attempted to characterize TRD. For example, in Europe, the European Group for the Study of Resistant Depression has published several studies and reviews Kautzky et al, 2019;Schosser et al, 2012;Souery et al, 2007) Our narrative review indicated that no consensus definition existed for TRD. We identified four basic definitions for TRD (three for MDD, one for bipolar disorder).…”
Section: Discussionmentioning
confidence: 93%
“…For example, in Europe, the European Group for the Study of Resistant Depression has published several studies and reviewsKautzky et al, 2019;Schosser et al, 2012;Souery et al, 2007) that have influenced current treatment recommendations of the European Medicines Agency (European Medicines Agency, 2013). We assessed how well this available literature addressed two main questions: what was the consensus definition for TRD, and how this definition applied in intervention trials.…”
mentioning
confidence: 99%